Enhancing wear resistance of Cu–Al alloy by controlling subsurface dynamic recrystallization. (May 2015) - Chen, X.; Han, Z.; Lu, K.
Abstract : The sliding wear resistance of Cu-2.2 wt.% Al alloy can be remarkably enhanced by controlling subsurface dynamic recrystallization (DRX) process. The wear volume decreases from 3.1 × 10 7 to 0.9 × 10 7  μm 3 when the DRX grain size increases from 0.28 to 0.62 μm induced by dynamic plastic deformation and subsequent annealing. The enhanced wear resistance stems from a wear mechanism transition from cracking and peeling-off of the fine-grained DRX layer to that of the topmost nanostructured mixing layer as DRX grains become coarser.